2022
DOI: 10.1111/jocn.16393
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early postoperative indwelling urinary catheter removal: A systematic review

Abstract: Background Indwelling urinary catheters (IDUCs) are associated with complications and early removal is therefore essential. Currently, it is unknown what the effect of a specific removal time is and what the consequences of this removal time are. Research question To present an overview of the available evidence to determine the effects of three postoperative IDUC removal times (after a certain number of hours, at a specific time of day and flexible removal time) on the development of complications in hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
(236 reference statements)
2
0
0
Order By: Relevance
“…Mobility challenges related to the IDUC, including prolonged time to ambulation (walking without the support of a nurse), immobility and discomfort, overlap with previous findings 36. In this study, patients reported feeling dependent on nurses’ directives which could have delayed the moment of mobilisation and thereby have a negative influence on the discharge date 37 38…”
Section: Discussionsupporting
confidence: 59%
“…Mobility challenges related to the IDUC, including prolonged time to ambulation (walking without the support of a nurse), immobility and discomfort, overlap with previous findings 36. In this study, patients reported feeling dependent on nurses’ directives which could have delayed the moment of mobilisation and thereby have a negative influence on the discharge date 37 38…”
Section: Discussionsupporting
confidence: 59%
“…However, the risk of infection associated with these catheters is a critical concern. Therefore, numerous studies, including recent systematic reviews, have highlighted the importance of promptly removing unnecessary central venous and urinary catheters in order to prevent catheter-associated infections [39][40][41][42]. In our study, there were significantly decreased indwelling periods of the central and urinary catheters in the after-FD group.…”
Section: Discussionsupporting
confidence: 46%
“…With the advancement of minimally invasive technology and the promotion of the ERAS concept, increasing evidence supports the expedient removal of catheters and the absence of urinary indentations after surgery [13,14]. Due to problems such as high renal pelvic pressure and low lithotripsy e ciency, traditional ureteroscopy is prone to postoperative complications such as infection and bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the longer the catheter retention time, especially > 2 days, the greater the probability of patients developing catheter-associated UTIs [17,18]. Early removal of unnecessary urinary catheters, either immediately or after 1-2 days, does not result in higher recatheterization rates, whereas immediate removal leads to earlier activity and a shorter hospital stay [13,19,20].…”
Section: Discussionmentioning
confidence: 99%